Synthesis, Structure and Alkylation of 4-(4-Fluoro phenyl)-5-(isomeric pyridyl)-1,2,4-triazole-3-thiole - Seyyed Shahabi, Soulmaz; Gharibi, Mahtab (Asian Journal of Chemistry, 2012)
New 3,5-disubstituted-1,2,4-triazole and their derivatives 3(a-c) were synthesized in excellent yield by the intra molecular cyclization of 1,4-disubstituted thiosemicarbazides 2(a-c) with sodium hydroxide. Their further alkylation with methyl iodide in OH- medium led to the formation of biologically active 4(a-c). These new compounds have been characterized by MS, 1H NMR and IR spectroscopy. In addition, the yield and reaction time of 4(a-c) have been compared with gently reflux and ultrasonic bath ways.